Credit sources, access and factors influencing credit demand among rural livestock farmers in Nigeria - Gadanakis, Yiorgos; Kotugan Fada Silong, Asenath (My University, 2019)
Purpose – Rural farmers’ access to farm credit in Nigeria has been very low, which affects farm performance, and credit providers have blamed for the problem in the sector. While this general perception persists the fact may be the case of credit demand, rather than just the risk-averse attitudes of credit providers. The purpose of this paper is to investigate significant factors influencing farmers’ credit demand to ensure efficient credit provision. Design/methodology/approach – The research adopted mixed methods for an in-depth investigation into the problem. There were 216 research participants split into equal halves of men and women from six local government areas of Nasarawa State. Data collection methods employed structured interviews, focus group discussions, close/open-ended and key informant interviews. Analytical tools involved descriptive statistics, the logit and multinomial logit models to determine participants’ socio-economic characteristics, sources of credit, access, factors influencing credit demand generally and from the various sources of credit identified. Findings – Findings reveal only 47.6 per cent of the participants accessed credit, with fewer women accessing than men. The most accessed forms of credit are from the semi-formal sources, with more men accessing from formal sources and more women from non-formal sources. Factors having significant influence on credit demand generally are education, group membership and household size. And from formal, semi-formal and non-formal credit sources are education, information on sources of credit, deposits, household size and marital status; education, deposits, group membership, household size, flock size; and education, group membership, and gender from the non-formal credit providers, respectively. Research limitations/implications – Due to time constraint, this study data were collected concurrently with both quantitative and qualitative methods and did not allow for the interrogation of findings from one method with the other. In addition, the research categorised the agency of women based on marital status only as single or married and did not interrogate the agency of women further, this may be a limitation as some of the female participants are from polygamous homes. Originality/value – Unlike the current concentration of Nigerian research of this kind with quantitative methods alone, this research contributes particularly to Nigerian research output and experience by triangulating both quantitative and qualitative methods to explore farmers sources of credit, access and factors determining access to credit in the study area.
Keywords: Rural Farmers; Logit model; Livestock production; Multinomial logit model; Credit demand